Sirtuin 6 Modulates Hypoxia-Induced Autophagy in Nasal Polyp Fibroblasts via Inhibition of Glycolysis. Issue 3 (May 2016) - Shun, Chia-Tung; Lin, Sze-Kwan; Hong, Chi-Yuan; Lin, Chih-Feng; Liu, Chia-Ming
Background: To elucidate the interaction between hypoxia-induced autophagy and glycolysis in nasal polyp fibroblasts, and the regulatory role of Sirtuin 6 (SIRT6) in the pathogenesis of nasal polyp. Objective: Through examining the expressions of lactate dehydrogenase (LDH), microtubule-associated protein II light chain 3 (LC3II) (an autophagy marker), and production of lactate under hypoxia, the interaction between autophagy and glycolysis was investigated. The role of SIRT6 on the hypoxia-induced autophagy and glycolysis was also examined. Methods: Nasal polyp specimens were used to examine the expressions of hypoxia-inducible factor (HIF) 1α, LDH, and LC3II by Western blot analysis, and primary cultures of nasal polyp fibroblasts were established from resected nasal polyps to measure hypoxia-induced LDH and LC3II expression by Western blot analysis and lactate production by colorimetry. Forced expression of SIRT6 with a lentiviral-based technique was used to evaluate its suppressive effect on autophagy and glycolysis. Immunohistochemical staining was performed to detect the expressions of SIRT6, LDH, and beclin (another autophagy marker) in nasal polyps. Results: Expression of HIF-1α, LDH, and an autophagy marker, LC3II, are increased in nasal polyp specimens, and forced expression of SIRT6 in nasal polyp fibroblasts inhibited LDH expression, lactate production under hypoxia, and SIRT6. An immunohistochemistry study of nasal polyp showed that SIRT6 expression was reduced and LDH and beclin were enhanced. Conclusion: Analysis of these data indicated that hypoxia may contribute to the formation of nasal polyp by promoting autophagy in nasal polyp fibroblasts. Through the antiglycolytic activity of SIRT6, the autophagy was suppressed, which was beneficial to nasal polyp formation. Modulation of glucose metabolism through SIRT6-based strategy may possess therapeutic potential for nasal polyposis in the future.